Colonic Mucosa With Polypoid Hyperplasia: A Pathologic and Molecular Reassessment of Endoscopically Apparent but Histologically Subtle Polyps and a Reappraisal of So-Called Goblet-Cell Rich Hyperplastic Polyps. Issue 4 (1st June 2019) - Hissong, Erika; Fernandes, Helen; Jessurun, Jose
Abstract: Objectives: Define the morphologic and molecular features of colonic polyps with subtle histologic features. Methods: Two hundred specimens were obtained of surveillance colonoscopies. Endoscopic findings were reviewed. Histologic features of the polyps were compared with the flat mucosa. Next-generation sequencing was performed on 30 study polyps and 20 control samples. Results: Polyps with subtle changes comprised 12% of all polyps. All polyps were sessile and small (<0.5 cm) and were located predominantly in the distal colon (60%). Synchronous hyperplastic, sessile serrated, and dysplastic polyps were found in 30%, 7%, and 51% of patients, respectively. A total of 169 (84.5%) polyps showed wide, nonserrated crypts, increased intraluminal mucus, and patent openings. KRAS alterations were present in 30% of polyps. Conclusions: Most polyps with subtle histologic features have recognizable morphologic changes. About one-third harbored KRAS alterations. These polyps should not be regarded as variants of hyperplastic polyps.